2019
DOI: 10.1111/prd.12318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes on periodontal diseases

Abstract: The susceptibility and severity of periodontal diseases is made more severe by diabetes, with the impact on the disease process inversely proportional to the level of glycemic control. Although type 1 diabetes mellitus and type 2 diabetes mellitus have different etiologies, and their impact on bone is not identical, they share many of the same complications. Studies in animals and humans agree that both forms of diabetes increase inflammatory events in periodontal tissue, impair new bone formation, and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
200
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(215 citation statements)
references
References 142 publications
(313 reference statements)
5
200
0
10
Order By: Relevance
“…Periodontal ligament degradation and alveolar bone loss indicate that the periodontium has lost its homeostasis capacity under inflammation (Graves et al 2019). Several studies have shown that PDL stem cells from patients with periodontitis display changes in proliferation and differentiation potential and cell migration capacity (Zhang et al 2012).…”
Section: Histone Methylation Alteration In Periodontal Disease: Animamentioning
confidence: 99%
“…Periodontal ligament degradation and alveolar bone loss indicate that the periodontium has lost its homeostasis capacity under inflammation (Graves et al 2019). Several studies have shown that PDL stem cells from patients with periodontitis display changes in proliferation and differentiation potential and cell migration capacity (Zhang et al 2012).…”
Section: Histone Methylation Alteration In Periodontal Disease: Animamentioning
confidence: 99%
“…Confirming the role of SETD1 in p65-mediated periodontal inflammation, the IKK2 inhibitor BOT-64 reduced the number of SETD1-positive cells in inflamed periodontal tissues, restored periodontal tissue integrity, and enhanced osteogenesis in a periodontal inflammation model in vivo. Based on the inhibitory effect of inflammation on osteogenic potential of mesenchymal stem cells (Lacey et al 2009, Graves et al 2019), we expect that NF-κB signaling inhibitors such as BOT-64 display similar effects on SETD1 function in terms of gene regulation. In the present study, we successfully introduced the IKK2/NF-κB activation inhibitor BOT-64 to enhance osteogenic differentiation of PDL cells in the subcutaneously implanted collagen sponges and to facilitate alveolar bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes affected bacteria-host interactions to promote inflammation and periodontal disease. 23 The inflammatory response modified oral microbiota to render it more pathogenic. Complement system may also be involved in the process.…”
Section: Discussionmentioning
confidence: 99%